2019
DOI: 10.1093/jpe/rtz041
|View full text |Cite
|
Sign up to set email alerts
|

Climatic niche shift of an invasive shrub (Ulex europaeus): a global scale comparison in native and introduced regions

Abstract: Aims Invasive species, which recently expanded, may help understand how climatic niche can shift at the time scale of the current global change. Here, we address the climatic niche shift of an invasive shrub (common gorse, Ulex europaeus) at the world and regional scales to assess how it could contribute to increasing invasibility. Methods Based on a 28 187 occurrences database, we used a combination of 9 species distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 47 publications
4
45
0
1
Order By: Relevance
“…Hernández-Lambraño et al, 2016) and has shown that gorse is far from having filled its potential niche, confirming that its geographical expansion capacity is still important (Hill et al, 2008). We have extended this analysis of the bio-climatic niche to the global level, which allows us to estimate the level of adequacy of the local climate of all regions of the world with the ecological needs of gorse (Christina et al, 2019).…”
Section: Introductionmentioning
confidence: 62%
“…Hernández-Lambraño et al, 2016) and has shown that gorse is far from having filled its potential niche, confirming that its geographical expansion capacity is still important (Hill et al, 2008). We have extended this analysis of the bio-climatic niche to the global level, which allows us to estimate the level of adequacy of the local climate of all regions of the world with the ecological needs of gorse (Christina et al, 2019).…”
Section: Introductionmentioning
confidence: 62%
“…To analyze the factors that may explain the value of this indicator, we identified and estimated a set of explanatory variables. The choice of the explanatory variables tested was based on our previous work on gorse, in biology [36,40], history [32,41], and sociology [29]. These variables had to be both relevant and available in a standardized way for all the countries studied.…”
Section: Construction Of An Indicator Of the Invasive Statusmentioning
confidence: 99%
“…At large geographical scales, climate is considered to act as the main filter of invasive species distribution [42,43]. To estimate the proportion of the country where the climate fulfills the requirements of gorse, we used the results of the global Species Distribution Model (SDM) of the bioclimatic niche of gorse designed by our team [36]. According to the literature, we retained the presence probability threshold calculated using the maximum likelihood [44].…”
Section: Construction Of An Indicator Of the Invasive Statusmentioning
confidence: 99%
See 2 more Smart Citations